A microfabricated fixed path length silicon sample holder improves background subtraction for cryoSAXS. (1st February 2015) - Hopkins, Jesse B.; Katz, Andrea M.; Meisburger, Steve P.; Warkentin, Matthew A.; Thorne, Robert E.; Pollack, Lois
<x xml:space="preserve">Abstract</x> The application of small‐angle X‐ray scattering (SAXS) for high‐throughput characterization of biological macromolecules in solution is limited by radiation damage. By cryocooling samples, radiation damage and required sample volumes can be reduced by orders of magnitude. However, the challenges of reproducibly creating the identically sized vitrified samples necessary for conventional background subtraction limit the widespread adoption of this method. Fixed path length silicon sample holders for cryoSAXS have been microfabricated to address these challenges. They have low background scattering and X‐ray absorption, require only 640 nl of sample, and allow reproducible sample cooling. Data collected in the sample holders from a nominal illuminated sample volume of 2.5 nl are reproducible down to q≃ 0.02 Å−1, agree with previous cryoSAXS work and are of sufficient quality for reconstructions that match measured crystal structures. These sample holders thus allow faster, more routine cryoSAXS data collection. Additional development is required to reduce sample fracturing and improve data quality at low q.